1969
DOI: 10.1017/s0021859600014386
|View full text |Cite
|
Sign up to set email alerts
|

Blood potassium and haemoǵlobin polymorphism in Indian sheep

Abstract: Blood potassium and haemoglobin types were investigated in three breeds of sheep in India. Both high and low blood potassium types and all three haemoglobin types -A, B, and AB-were found to be present in two of the breeds examined, namely Bikaneri and Corriedale x Bikaneri. Mandia sheep had both potassium types but only two haemoglobin types-B and AB. Haemoglobin B and high potassium types predominated in all the three breeds; this would clearly point to the comparative suitability of these animals for relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

1973
1973
1994
1994

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 15 publications
1
19
1
Order By: Relevance
“…For the M system (frequently described only in terms of high or low blood potassium) and the Tf and Hb loci wide variations in frequencies are to be found in other reports (see Agar, Evans and Roberts, 1972;Stormont et al, 1968). Explanations based on adaptation to particular environments have been put forward but the present data are not suitable to test such hypotheses.…”
Section: Correlations Between Blood Group Locimentioning
confidence: 70%
“…For the M system (frequently described only in terms of high or low blood potassium) and the Tf and Hb loci wide variations in frequencies are to be found in other reports (see Agar, Evans and Roberts, 1972;Stormont et al, 1968). Explanations based on adaptation to particular environments have been put forward but the present data are not suitable to test such hypotheses.…”
Section: Correlations Between Blood Group Locimentioning
confidence: 70%
“…In experiment 5, the same trend was observed (figure 2), but the difference between the 2 groups was not significant ( (Blum and Cioli, 1978;Deelder et al, 1978;Perrudet-Badoux et al, 1978;Wakelin, 1978 (Evans et al, 1963;Jilek and Bradley, 1969;Radhakrishnan et al, 1972;Allonby and Urquhart, 1976;Dargie, 1976, 1978a, b;Preston and Allonby, 1979;Dally et al, 1980;Luffau et al, 1981a, b;Courtney et al, 1985), but they are in keeping with the results of Le Jambre (1978), R,iffkin and Dobson (1979), Courtney et al (1984), Riffkin and Yong (1984) Evans and Whitlock (1964), Radhakrishnan et al (1972), Dargie (1976, 1978a, b) and Albers and Burgess reported by Piper (1987). The post-infection differences observed between animals of various haemoglobin genotypes might simply be due to differences existing in non-infected animals (Agar et al, 1972). These differences might arise from oxygen affinity differences between haemoglobins A and B. Haemoglobin A has a higher oxygen affinity: at equal pressure, it releases less oxygen, which might cause the creation of compensatory mechanisms in haemoglobin A carriers (Agar et ad, 1972 (1984, 1985, 1986, 1987 and 1988) who found an association between the OLA system and the response to a vaccination against Trichostrongylus colubrifo!rmas.…”
Section: Effect Of Anthelmintic Treatment On Immunity To the Parasitementioning
confidence: 99%
“…In the previous works it has been stated that the potassium blood level in sheep is genetically controlled by two alleles K L and K H , the second one recessive (Agar et al, 1972;Bhat et al, 1981;Bojczuk, 1987;Kumar, 1984;Lazovski and Spiridonov, 1974;Lipecka et al, 1987;1991). Homozygotes of the K H gene are characterized by a high potassuim level in blood (level HK), while those of the K L gene and heterozygotes by a low potassium blood level (level LK).…”
Section: Introductionmentioning
confidence: 99%
“…These studies have also proved that there is a considerable differentiation between breeds, kinds, and even a differentiation within a breed between flocks in the frequency of occurrence of genes and phenotypes. Simultaneously the potassium level is reflected in differentiated physiological and biochemical changes (Agar et al, 1972). This can affect the productivity level of animals, constituting a certain selective index.…”
Section: Introductionmentioning
confidence: 99%